Analysis of Islamic Supply Chain Strategies in Indonesia - Yuhanis Ladewi; Antoni Antoni; Mizan Mizan; Rima Melati (International Journal of Supply Chain Management, 2020)
Abstract- This conceptual paper is aimed to explore critical factors of the Islamic supply chain for their economic impact in the region of Indonesia. The variable used in this study is the strategy of Halal supply chain and optimizing the potential of economy. The data analysis used was qualitative descriptive. The results of the research carried out were the supply chain strategy carried out by the Halal management institution in Palembang, namely by establishing halal strategy collection units which were placed in several government agencies such as government agencies and companies as well as cooperating with banks, government officials, and religious leaders. The strategy for halal supply chain can be done by OPZ, LAZIS or BAZIS through the payment system, among others; supports from government and private; halal hub; differentiation between Muslim and non-Muslim suppliers; halal control and labeling; also be paid through Islamic banking services. We highlighted that in fulfilling the orders from customer, complete segregation between halal and non-halal products throughout the supply chain is strictly required. The manufacturing flow management is about physical handling of the products that must be controlled from the origin to the consumption points. In addition, procurement also plays an important role in the supply chain, which is according to Tieman et al. (2012), to define and manage the upstream supply chain networks. It covers purchasing strategy, selection of suppliers, ordering, evaluating suppliers, and determining the specification